2020
DOI: 10.1111/exd.14185
|View full text |Cite
|
Sign up to set email alerts
|

Stratum corneum lipidomics analysis reveals altered ceramide profile in atopic dermatitis patients across body sites with correlated changes in skin microbiome

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 42 publications
4
58
0
2
Order By: Relevance
“…74 Interestingly, site-specific lipid alterations and correlations with the skin microbiota were also reported in AD. 75 The correlation analysis of skin lipid alterations with the microbiota showed that Staphylococcus S. epidermidis and C. acnes was lower than in healthy skin. 77 Psoriasis skin was also shown to be associated with an increased abundance of Firmicutes and a corresponding reduction in Actinobacteria, most marked in lesional skin in a prospective observational study performed by 16S rRNA sequencing.…”
Section: Atopic Dermatitismentioning
confidence: 98%
“…74 Interestingly, site-specific lipid alterations and correlations with the skin microbiota were also reported in AD. 75 The correlation analysis of skin lipid alterations with the microbiota showed that Staphylococcus S. epidermidis and C. acnes was lower than in healthy skin. 77 Psoriasis skin was also shown to be associated with an increased abundance of Firmicutes and a corresponding reduction in Actinobacteria, most marked in lesional skin in a prospective observational study performed by 16S rRNA sequencing.…”
Section: Atopic Dermatitismentioning
confidence: 98%
“…These studies have shown that the strongest influence on the skin microbiome stems from the local skin microenvironment, in particular determined by skin pH, skin hydration, sebum production and epidermal lipid content. 69,70 Additionally, links between the skin microbiome or its members and a variety of intrinsic and extrinsic factors have been observed, including age, 57,71,72 sex, 73,74 BMI, 75 use of cosmetic products, 76,77 exposure to antibiotics, 78 ethnicity and geographical region. [79][80][81] Moreover, variation in the skin microbiome was found to be associated with several environmental factors, including UV exposure, 82 exposure to domestic animals such as dogs, 83 contact with soil and plants, 84 and urbanization of place of residence.…”
Section: Skin Microbiome In Psoriasismentioning
confidence: 99%
“…AD is characterized by a dysfunctional epidermal barrier and skin microbiome dysbiosis 20 . To determine whether abnormalities in epidermal lipid organization and microbiome composition are correlated in AD, tape stripped samples were collected from AD patients and healthy volunteers across different body sites for lipidomic characterization and bacterial 16 rRNA sequencing 33 . The results showed that Staphylococcus aureus colonization is positively correlated with site‐specific lipid alterations in AD, suggesting that staphylococcal over‐colonization may impair skin barrier function also by altering epidermal lipid composition.…”
Section: Disease Aetiologymentioning
confidence: 99%